Appropriate use of echocardiography for palpitations in paediatric cardiology clinics. (7th January 2021) - Sheth, Saloni; Fares, Munes; Kikano, Sandra; Snyder, Christopher; Dodgen, Andrew; Wilhelm, Carolyn M.
Abstract: Objectives: Identify diagnostic yield and frequency of echocardiograms for palpitation-related indications at outpatient paediatric cardiology clinics in relation to the 2014 ACC/AAP/AHA/ASE/HRS/SCAI/SCCT/SCMR/SOPE appropriate use criteria for Initial Transthoracic Echocardiography in Outpatient Paediatric Cardiology. Study design: A single-centre, retrospective study of children presenting for evaluation of a chief complaint of palpitations to outpatient paediatric cardiology clinics from 2015 to 2017. Palpitations were defined as an unpleasant sensation of rapid, irregular, and/or forceful beating of the heart. Indications for echocardiogram in patients were retrospectively classified based on the appropriate use criteria as "appropriate, " "may be appropriate, " or "rarely appropriate." The incidence of abnormal and incidental echocardiographic findings for each category was determined. Results: A total of 286 patients presented with palpitations, with 128 (52% female) meeting inclusion criteria. Exclusion criteria included patients with additional cardiac complaints, prior echocardiogram, or history of congenital heart disease. Echocardiograms were performed on 36 (28%) patients. The appropriate use criteria were retrospectively applied, and indications for their performance were classified as "appropriate" (n = 4), "may be appropriate" (n = 17), or "rarely appropriate" (n = 15). Minor echocardiographic abnormalities were present in 22% (n = 8) of echocardiograms obtained for all appropriate use criteria classifications. No moderate or severe echocardiographic abnormalities were found. Incidental findings were noted in eight echocardiograms. Conclusion: Echocardiography in the evaluation of "rarely appropriate" and "may be appropriate" palpitation-related indications is of low diagnostic yield.